2007
DOI: 10.1007/s11013-007-9066-y
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in the Experience of Everyday Symptoms: A Comparative Study of South Asian and European American Women

Abstract: This paper describes a study of medically ambiguous symptoms in two contrasting cultural groups. The study combined a qualitative, meaning-centered approach with a structured coding system and comparative design. Thirty-six South Asian immigrants and thirty-seven European Americans participated in a semistructured health history interview designed to elicit conceptual models of medically unexplained illness. The groups reported similar symptoms, but the organization of illness episodes and explanatory models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…2,4,12 Studies conducted in the UK, the U.S., and India that have examined predictors of depression and similar conditions concluded that older age, literacy, financial difficulties, 12 gender roles, 21 perceptions of illness, 3 social isolation, and poor physical health 1 were contributory factors. Language, feelings of isolation, and lack of adherence to mental health treatment regimens, which are often seen as unnecessary, inhibit proper treatment.…”
Section: Resultsmentioning
confidence: 99%
“…2,4,12 Studies conducted in the UK, the U.S., and India that have examined predictors of depression and similar conditions concluded that older age, literacy, financial difficulties, 12 gender roles, 21 perceptions of illness, 3 social isolation, and poor physical health 1 were contributory factors. Language, feelings of isolation, and lack of adherence to mental health treatment regimens, which are often seen as unnecessary, inhibit proper treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Despite broad variations in language, religion, diet, etc., most scholars agree that societies of South Asia, particularly those of the ‘purdah belt,’ a broad region stretching across the northern part of India that includes Pakistan and Bangladesh, broadly constitute a culture area that shares many social, structural and cultural characteristics. The Tension Scale we developed for the study includes symptoms that have been reported in studies of other South Asian groups (24, 49, 71-73). However, the degree to which the scale is appropriate for use with other groups is an empirical question that will be answered in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The term ‘depression’ was discussed in turn, and dismissed as a rare, severe disorder in which people acted ‘pagal’ (crazy). The syndrome that was chosen to work on was ‘tension,’ a common illness category in South Asia that is frequently reported in the literature, including the previous work of the first author ((49)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies examining the stigma of mental illness experienced by Chinese individuals in the context of family, community, and personal belief have confirmed this theory (Lam et al, 2010, Leong & Lau, 2001Lin & Lin, 1981). Furthermore, Asian individuals residing in Western nations, compared to European counterparts, tend to explain depressive symptoms as social and moral problems (Karasz, 2005;Karasz, Dempsey, & Fallek, 2007;Xu et al, 2013. These findings were also present in examinations of the Japanese culture, as their culture greatly values group approval -especially from the family -and mental illness is viewed as a source of shame (Samuma, 1978).…”
Section: "Face" and The Stigma Of Mental Illness In Asian Individualsmentioning
confidence: 93%